Evaluation of the Moisturizing Efficacy and Stability of an Essence Sheet Mask Formulated with Red Dragon Fruit (Hylocereus polyrhizus) Peel Extract - Al Mu’izzah, Nurul; Desy Nawangsari; Adita Silvia Fitriana (HM Publisher, 2024)
The pursuit of effective and natural skincare solutions has led to the exploration of plant-based ingredients. Red dragon fruit (Hylocereus polyrhizus) peel, rich in flavonoids and antioxidants, presents a promising avenue for developing moisturizing skincare products. This study aimed to evaluate the moisturizing efficacy and stability of an essence sheet mask formulated with red dragon fruit peel extract. Red dragon fruit peel extract was obtained using ethanol extraction. Essence sheet masks were formulated with varying concentrations of the extract (0%, 3%, 5%, and 7%). The physical properties (organoleptic characteristics, pH, viscosity, and homogeneity), stability (cycling test), skin irritation potential (patch test), and moisturizing efficacy (corneometer measurements) of the sheet masks were assessed. The hedonic attributes of the masks were also evaluated through a consumer perception study. The formulated essence sheet masks exhibited desirable physical properties and were stable under accelerated storage conditions. No skin irritation was observed in the patch test. The sheet masks containing red dragon fruit peel extract demonstrated a significant increase in skin hydration compared to the control group. The consumer perception study indicated high acceptance of the masks, particularly those with higher extract concentrations. The findings suggest that red dragon fruit peel extract can be effectively incorporated into essence sheet masks to enhance skin hydration. The developed sheet masks were well-tolerated and exhibited good stability, making them promising candidates for natural moisturizing skincare products.